The Legal Provisions of the Arbitral Award of Electronic Arbitration With respect to the International Conventions and UAE Law - ZAINEDDIN, MARWAN SALA SALMAN (2018)
In the current business and market setting where everything is now online, new challenges have emerged in terms of how the traditional means of doing business can successfully translate to the electronic world. In terms of related laws, numerous countries have implemented appropriate laws to implement electronic arbitration. Thus far, these efforts have included electronic laws from Egypt, Jordan, UAE, Qatar, Europe, the UK, and the US. International Conventions have also been set forth to serve as guide in the implementation of electronic arbitration. These laws have managed to set forth the necessary terms of electronic arbitration including its manner of implementation, its coverage, and its related terms and conditions. Arbitral awards have helped provide settlement and justice for legal concerns in the digital setting. This paper presents the definition of electronic arbitral awards, its conditions as well as requirements. It also presented the effects of these awards, and the fact that these awards can be considered res judicata. The enforcement of electronic arbitral awards are also presented in relation to international conventions as well as national laws. Lastly, the enforcement of the electronic awards in accordance with self-implementation is also indicated in this paper.